Implementation of a Program for Improving Nutrition for Toddler in Sei Kasih Village, Bilah Hilir District, Labuhan Batu District - Susiani; Ti Aisyah; Syamsuddin; Murniati; Asrul Fahmi (PT PUSTAKA CENDEKIA GROUP, 2024)
This research was conducted in Sei Kasih Village, Bilah Hilir District, Labuhan Batu Regency, to determine the implementation of a nutrition improvement program for toddlers in the area. The implementation of the nutritional improvement program for toddlers in Sei Kasih Village, Bilah Hilir District, Labuhan Batu Regency is still not optimal. This is because there are still several problems, namely the provision of additional food (PMT) which is charged, there are still posyandu cadres who do not understand about providing additional food and the facilities are inadequate. Village budget funds amount to Rp. 7,800,000 per year is used to pay salaries for toddler posyandu cadres and additional food consumption. However, these funds are still insufficient because toddlers' visits to posyandu are erratic. This research uses qualitative methods with data collection techniques including observation, interviews and documentation. The data analysis techniques include data reduction, data presentation and drawing conclusions. The results of the research show that there are still children who are malnourished, and other problems are the lack of guidance and lack of communication between posyandu cadres and parents of toddlers. There are 2 nutrition improvement programs implemented, namely toddler health service activities and providing additional food. This research hopes to contribute to improving the nutritional quality of children under five in the region.